THE STUDENT´S INTEGRATED TECHNICAL COURSES VOICE! PERCEPTIONS ABOUT REMOTE ACTIVITIES DURING THE COVID 19 PANDEMIC - da Cunha, Fanley Bertoti [UNESP]; de Freitas, Kelma Cristina; Pescumo, Fernanda Franzoni; Dos Santos, Ivan Luis (Revista Pesquisa Qualitativa - RPQ, 2022)
The aim of this study is to investigate the students' perceptions regarding access to Emergency Remote Education (ERE) during the Covid-19 pandemic. Students were from two integrated courses from a campus of IFSP. During the offer of the ERE, teachers proposed non-obligatory complementary activities (NOCAs) to the students. In addition, they sent digital questionnaires referring to NOCAs. Students’ responses were qualitatively explored with the Content Analysis technique, using NVivo® software. We identified three categories through the questionnaire exploration: (anti)conditions of studies in pandemic reality, (contra)conditions of teacher pedagogical support, and (re)production of school holes and school knowledge. We consider that in a moment of suspension of face-to-face activities, the NOCAs allowed the maintenance of school bonds with the students. However, this interaction requires evaluation to avoid a banking model of education.
OS ESTUDANTES DO ENSINO MÉDIO INTEGRADO FALAM! PERCEPÇÕES SOBRE ATIVIDADES REMOTAS REALIZADAS DURANTE A PANDEMIA DE COVID 19
Keywords: Access to education; Emergency Remote Education; Federal Institute; Integrated Professional Education